NO2 emissions from agricultural burning in São Paulo, Brazil - Oppenheimer, C.; Tsanev, VI; Allen, A. G.; McGonigle, AJS; Cardoso, Arnaldo Alves [UNESP]; Wiatr, A.; Paterlini, W.; De Mello, C. (Amer Chemical Soc, 2004)
We report here on the application of a compact ultraviolet spectrometer to measurement of NO2 emissions from sugar cane field burns in São Paulo, Brazil, the time-resolved NO2 emission from a 10 ha plot peaked at about 240 g (NO2) s(-1), and amounted to a total yield of approximately 50 kg of N, or about 0.5 g (N) m(-2). Emission of N as NOx (i.e., NO + NO2) was estimated at 2.5 g (N) in 2, equivalent to 30% of applied fertilizer nitrogen. The corresponding annual emission of NOx nitrogen from São Paulo State sugar cane burning was >45 Gg N. In contrast to mechanized harvesting, which does not require prior burning of the crop, manual harvesting with burning acts to recycle nitrogen into surface soils and ecosystems.